Modelo analítico de governança colaborativa e adaptativa de problemas perversos em sistemas sócio-ecológicos - Andrade, Raphael de Jesus Campos de (2019)
This research has the main purpose of developing an analytical model of collaborative and adaptive governance of perverse problems for building resilience in socio-ecological systems affected by industrial disasters. Wicked problems are social and political planning dilemmas that resist clear definitions and predetermined sets of natural science and engineering solutions. Industrial disasters are phenomena that assume the condition of wickedness when they affect human welfare and the ability to provide ecosystem services, weakening the bond that constitutes them as a socio-ecological system. Approaches to collaborative and adaptive public governance are increasingly recognized in this gradation as the most conducive means of dealing with wicked problems in the context of industrial disasters. A case study related to the recovery process of the Rio Doce Basin, resulting from the Samarco mining disaster, was carried out. Occurred on November 2015 due to the rupture of the Fundão tailings dam in Minas Gerais, this was the largest environmental disaster in Brazil and the largest in the world involving tailings dams. In order to understand this phenomenon, a preliminary framework for governance of wicked industrial disasters was built, based on institutional theory and composed of elements of wicked problem literature and collaborative and adaptive governance. To apply this framework and operationalize this study, a socio-ecological inventory was done – a methodology created to increase the adaptation of policy networks to extreme changes from different phases, methods, techniques and research instruments. In this regard, the research stands out the use of bibliographic and documentary research, interviews supported by a semistructured script, network sampling and direct observation, the application of the conversation analysis method for data categorization and the use of abductive logic for the systematic combination of theoretical categories with empirical observations. Thus, it was possible to reformulate the research framework and then propose the definitive governance model of wicked industrial disasters for the generation of socio-ecological adaptation. In addition, the applicability of the proposed analytical model was confirmed by characterizing the process of recovery of the Rio Doce Basin in terms of its institutional design conditions, knowledge, leadership and structural arrangements, which together determined the learning levels. established social. It was observed that in Samarco’s case the attempt to resume fishing activity at the mouth of the Rio Doce and surrounding areas was the problem that most concentrates the characteristics of wickedness. In this context, it was found that the levels of social learning obtained were not enough to constitute a governance regime capable of coordinating the multiplicity of emerging interests. Thus, two conflicting institutional logics were established. One aimed at defending Samarco’s interests and the other at recognizing the rights of affected communities. Among the results of this power struggle several fishermen invested their compensation in intensifying fishing activity, causing the imminent risk of the ichthyofauna collapse and deepening the wickedness of the disaster.